2006
DOI: 10.2146/ajhp050522
|View full text |Cite
|
Sign up to set email alerts
|

Survey of care provided by ambulatory care pharmacists to patients with chronic kidney disease

Abstract: The ambulatory care pharmacists surveyed were not consistently involved in the routine monitoring of common complications of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…8,[11][12][13][14][15] More specific to renal pharmacy, some renal pharmacists are not aware of evidence-based guidelines for clinical practice. 16 It is essential to close the know-do gap with respect to renal QI-DTPs, to ensure that patients with renal disease who have prevalent and impactful drug therapy needs receive high-quality pharmaceutical care. There has been some research on the interventions that renal pharmacists should perform, but there are few high-quality studies that address the effects of such interventions in renal patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,[11][12][13][14][15] More specific to renal pharmacy, some renal pharmacists are not aware of evidence-based guidelines for clinical practice. 16 It is essential to close the know-do gap with respect to renal QI-DTPs, to ensure that patients with renal disease who have prevalent and impactful drug therapy needs receive high-quality pharmaceutical care. There has been some research on the interventions that renal pharmacists should perform, but there are few high-quality studies that address the effects of such interventions in renal patients.…”
Section: Introductionmentioning
confidence: 99%
“…A survey [8] of pre-dialysis care indicated that only a small portion of ambulatory care pharmacists monitored the areas recommended by the Kidney Disease Outcomes Quality Initiative (K/DOQI) guidelines [9][10][11][12]. The delivery of CKD care, as monitored using administrative data, is suboptimal when compared to the guidelines recommendations [13].…”
Section: Introductionmentioning
confidence: 99%